Post-graduate scholars can publish Compended-Guides to the literature of their field using Knowledge-Step-Forums - Jewett,Don L (PeerJ Preprints, 2016)
"Publication forms the core structure supporting the development and transmission of scientific knowledge" (Galbraith2015). Yet, with the WorldWideWeb a dominant part of current scientific publication and information-dissemination, internet "publication" is still paper-based in its style and methods, even when it uses a digital medium. Such a paper-based publishing "model" is not adequate for a Web-based world. In 2006, an estimated 3,700 peer-reviewed scientific articles were published per day (Bjork2009)! This totals about 1.35 million articles per year. A similar estimate for 2011 was 1.8 million (Outsell2013), which is almost 5,000 per day. The total number of English-language scholarly documents accessible on the Web was estimated in 2014 to be at least 114 million (Khabsa2014). The methods and features described here are clearly needed now, and will be absolutely necessary in the future, when even more articles are published and available. In this context of an overload of information from scientific articles, described here is the idea of Knowledge-Step Forums as the basis for creating new peer-reviewed, compended "Literature-Guides", each on a very narrow topic and in a MultiLevel Format (Knowledge-Step Compendia). A multitude of Forum-Compendors, who need not be a senior faculty member (as is the case in traditional literature-reviews), but can be pre-docs, post-docs, and senior medical/surgical residents, will be aided by their mentors and online experts to create these Knowledge-Step Compendia. All participants (students and faculty) will be motivated by their own self-interest and thus each gains from the activity, it being a means to self-organize groups of like-minded scholars that can be the basis for reviews of new data, discovering new ideas, and finding jobs. The Software for Knowledge-Step Forums will also be useful to speed publication on the Web because it will easily support Publication Preprints with online peer-review.
Keywords: Compendium; Knowledge-Creation; Stronger Inference; Post-Graduate Education; MultiLevel-Format; Active Archive; PrePrint Publishing; Compending-Forum; Knowledge-Step; Compended Literature-Guide